Customer Journey Optimization With Design Thinking Method To Develop Costumer Relation And Loyalty At Distrik Berisik As Creative Agency - Fadhil Adam Dzaky (Green Publisher Indonesia, 2026)
Digitalization and rising demand for branded content have reshaped Indonesia’s creative industry over the past decade. The post-pandemic shift toward digital content, social media marketing, and integrated creative solutions has pushed agencies to innovate continuously. Competition has grown not only among established agencies but also with the rise of large-scale freelance collectives, making client loyalty a critical differentiator. Agencies now need to prioritize long-term, meaningful relationships rather than focusing solely on acquiring new clients. Distrik Berisik, a Jakarta-based creative agency founded in 2021, operates within this dynamic environment and serves Indonesia’s youth market with end-to-end creative solutions. Although customer acquisition is strong, the agency faces retention challenges, maintaining only a 30–40% retention rate. At the same time, many business leaders believe overly digital approaches often fail to align with real customer needs. This study addresses these issues by optimizing the customer journey through a Design Thinking approach. The research is guided by three questions: mapping the current customer journey from the first interaction to post-program stages; identifying key pain points and opportunities; and developing an improved journey model to strengthen customer experience and loyalty. A qualitative method is used, with Design Thinking’s five stages—Empathize, Define, Ideate, Prototype, and Test—serving as the main framework. Data were collected through questionnaires and analyzed using Thematic and Descriptive Analysis to reveal patterns, satisfaction levels, retention potential, and repurchase intentions. Combining the concepts of Customer Journey, Customer Loyalty, and Design Thinking, the study proposes a practical, human-centered customer journey model tailored to the creative industry.